2019
DOI: 10.22201/ia.14052059p.2019.51.21
|View full text |Cite
|
Sign up to set email alerts
|

Two-Station Meteor Observations With Mini-Megatortora and Favor Wide-Field Monitoring Systems

Abstract: Here we present the results of our four years long observations of meteors with Mini-MegaTORTORA wide-field monitoring system with sub-second temporal resolution. Over this period, we detected and catalogued more than 175000 faint meteors with magnitudes down to 8-10 mag and angular velocities up to 40 deg/s. Recently, we started double-station observations using Mini-MegaTORTORA together with reconstructed FAVOR camera on 3.8 km baseline. This setup allows to observe tens of faint meteors per night. We presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…However, we do not observe any streaking at any epoch, implying that the duration of each individual flash is much less than 1 second. This is consistent with the population of fast optical flashes noted in Biryukov et al (2015) and Karpov et al (2016), but observed in images integrated over minutes.…”
Section: Single-epoch Flash Samplesupporting
confidence: 89%
See 2 more Smart Citations
“…However, we do not observe any streaking at any epoch, implying that the duration of each individual flash is much less than 1 second. This is consistent with the population of fast optical flashes noted in Biryukov et al (2015) and Karpov et al (2016), but observed in images integrated over minutes.…”
Section: Single-epoch Flash Samplesupporting
confidence: 89%
“…where τ f is the equivalent width of the light curve and T exp is the exposure time. We assume a flash duration of 0.4 s, based on the mode of the distribution presented in Karpov et al (2016), when estimating the peak brightness from the observed magnitude.…”
Section: Magnitude Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to perform the laboratory and on‐sky characterization of this recently released camera, generously provided to us by the manufacturer for testing, in order to compare its properties with the ones of earlier sCMOSs (see Table for a brief comparison of parameters of Andor Marana with those of Andor Neo used here as a representative of a first‐generation sCMOS) and to assess its performance for sky survey applications. Such a device, if proven to be stable enough, may be of extreme importance for tasks of precise photometry in wide‐field sky surveys, especially when high temporal resolution is desirable, for example, for the detection and study of rapid optical transients (Karpov et al ; Karpov et al ), space debris tracking (Karpov et al ), or observations of faint meteors (Karpov et al ). Due to the large‐frame format, absence of microlens raster on top of the chip, good quantum efficiency, and fast readout, such a device may also be a promising detector for next‐generation f/(ph)otometric robotic atmospheric monitor (FRAM) atmospheric monitoring telescopes (Janeček et al ; Prouza et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Such a device, if proven to be stable enough, may be of extreme importance for a tasks of precise photometry in wide field sky surveys, especially when high temporal resolution is desirable, e.g. for the detection and study of rapid optical transients Karpov et al, 2010), space debris tracking (Karpov et al, 2016) or observations of faint meteors (Karpov, Orekhova, et al, 2019). Due to large frame format, absence of microlens raster on top of the chip, good quantum efficiency and fast read-out, such device may also be a promising detector for a next generation of FRAM atmospheric monitoring telescopes (Janeček et al, 2017;Prouza et al, 2010).…”
Section: Introductionmentioning
confidence: 99%